PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN INDRAGIRI HULU - Rosniati Rosniati; Mei Indrawati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
The purpose of this study was to find out and analyze together the performance of the employees of the Regional Development Planning Agency of Indragiri Hulu Regency. In addition to knowing and analyzing the motivation and results simultaneously on the performance of employees in of the Indragiri Hulu District. This type of research is explanative research or hypothesis testing research. The population in this study were all employees in the office in Bappeda of the Indragiri Hulu District 52 people with a sample of 51 people. The results showed that motivation and ability simultaneously had significant on the performance of employees in Bappeda of the Indragiri Hulu District. Motivation and ability variables partially had a significant influence on the performance of employees in Bappeda of the Indragiri Hulu District. Among the motivation and competency variables that has dominant influence on the performance of employees in Bappeda of the Indragiri Hulu District is motivation variable. Keywords: motivation, competency, performance